Optimalisasi Peran Karang Taruna Melalui Perancangan Kampanye Komunikasi Penanganan Sampah di Kecamatan Jalancagak Kabupaten Subang - Dhini Ardianti; Vera Hermawan; Lulu Nurul Muzkiyah; Antiq Elyana Febriyani (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2023)
The problem faced Karang Taruna Youth of Jalancagak District, Subang Regency is the lack of public awareness of the importance of protecting the environment and handling waste. Partners are not yet capable and understand waste management well due to limited information and communication approaches to the community so that environmental cleanliness has not yet been realized in Jalancagak District. The solution to solving this problem is to provide understanding by increasing environmental awareness through designing campaigns carried out by youth, from youth, for youth and citizens in general. The implementation method uses the PRA (Participation Rural Appraisal) approach which emphasizes community involvement or participation in the entire series of activities and increasing independence and internal strength in the community. The stages taken are providing assistance and also preparing a communication campaign design, starting with a pre-test through a questionnaire, then showing a documentary film about natural damage, and in the next stage assistance designing concepts, themes, messages, strategies and tactics, creating social media accounts, prepare content to share on those social media accounts. This is part of Karang Taruna's contribution as the nation's next generation in maintaining a clean environment in the digital era.